2002
DOI: 10.1152/ajpendo.00205.2001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and functional expression of somatostatin receptor subtypes in human thymocytes

Abstract: We recently demonstrated the expression of somatostatin (SS) and SS receptor (SSR) subtype 1 (sst1), sst2A, and sst3 in normal human thymic tissue and of sst1 and sst2A on isolated thymic epithelial cells (TEC). We also found an inhibitory effect of SS and octreotide on TEC proliferation. In the present study, we further investigated the presence and function of SSR in freshly purified human thymocytes at various stages of development. Thymocytes represent a heterogeneous population of lymphoid cells displayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…Most of the studies have been carried out using native SRIF, octreotide or lanreotide. Murine lymphocyte proliferation is inhibited in the same extent by lanreotide as native SRIF, indicating that the effect is mediated by sst 2 or possibly sst 3 (Agro et al, 1991 A c c e p t e d M a n u s c r i p t 7 thymocytes expressing sst 2 can be inhibited by octreotide whereas more differentiated thymocytes expressing sst 3 can be inhibited by SRIF and not by octreotide which has only a low affinity for sst 3 (Ferone et al, 2002).…”
Section: Effect Of Srif On the T Cell Lineagementioning
confidence: 94%
See 3 more Smart Citations
“…Most of the studies have been carried out using native SRIF, octreotide or lanreotide. Murine lymphocyte proliferation is inhibited in the same extent by lanreotide as native SRIF, indicating that the effect is mediated by sst 2 or possibly sst 3 (Agro et al, 1991 A c c e p t e d M a n u s c r i p t 7 thymocytes expressing sst 2 can be inhibited by octreotide whereas more differentiated thymocytes expressing sst 3 can be inhibited by SRIF and not by octreotide which has only a low affinity for sst 3 (Ferone et al, 2002).…”
Section: Effect Of Srif On the T Cell Lineagementioning
confidence: 94%
“…The expression of these different subtypes appears heterogeneous within the thymic tissue and on different cell subsets. A selective expression of sst 1 and sst 2 has been found on cultured thymic epithelial cells (TEC) (Ferone et al, 2002). TEC are thought to be a potential source of SRIF and CST production within the thymus, since their mRNA has been detected in these cells Ferone et al, 2002).…”
Section: Cortistatin Somatostatin and Their Receptors In The Human Imentioning
confidence: 99%
See 2 more Smart Citations
“…NOD diabetes is characterized by the invasion of lymphocytes, which destroy pancreatic B-cells (Hayakawa et al, 1991). It was demonstrated that lymphocytes express SSTR2, and SSTR3, and that the expression pattern of these SSTRs depends upon the degree of lymphocyte maturation (Ferone et al, 2002). Thus, the positive correlation of SSTR2 overexpression with the severity of insulitis could correlate with the degree of the lymphocyte invasion.…”
Section: Rodentsmentioning
confidence: 99%